A new approach to obtain a colour palette in thermographic images. Issue 1 (2nd January 2019) - Cruz-Albarran, Irving A.; Benitez-Rangel, Juan P.; Osornio-Rios, Roque A.; Dominguez-Trejo, Benjamin; Rodriguez-Medina, David A.; Morales-Hernandez, Luis A.
ABSTRACT: This work presents a methodology for automatic colour allocation in thermographic images which is based on two thermograms, one with an Iron colour palette for segmentation and the other in grayscale for thermal analysis through the thermal matrix. With the fusion of both procedures, a palette of colours image is obtained. The colour palette allows characterising the thermography in a controlled manner and gain a better interpretation of the colours. Likewise, the colour palette permits to work in temperature level. With this proposed methodology, it is possible to assign any colour desired. An experiment to induce human emotions (joy, disgust, anger, fear, and sadness) was carried out to prove the application of this proposed method. In a quantitative way, a thermal index of emotions that shows the emotion concerning the baseline was obtained, which correlates with the colours assigned to the new image. Each emotion was associated with one colour. The results attained from both the thermal index of emotions and the hue allocation show the applicability and validation of the proposed palette; thus, it could be employed in any application of thermographic analysis.